Red blood distribution width and heart transplantation: any predictive role on patient outcome?. Issue 3 (March 2019) - Lechiancole, Andrea; Sponga, Sandro; Vendramin, Igor; Valdi, Giulia; Ferrara, Veronica; Nalli, Chiara; Tursi, Vincenzo; Livi, Ugolino
Abstract : Background: Red blood cell distribution width (RDW) has been emerging as a strong predictor of mortality among patients with cardiovascular disease. The aim of this study was to verify if RDW is able to predict survival after heart transplantation (HTx). Methods: Two hundred and eighteen recipients who underwent HTx between 2000 and 2013 were classified into three groups according to the pre-HTx RDW tertile values (14.6 and 16.4%), and their outcomes were compared. Mean follow-up was 6.6 ± 4.2 years. Results: RDW correlated with other markers of chronic pathological conditions, such as the Index for Mortality Prediction after Cardiac Transplantation (IMPACT) score ( P = 0.002) and Charlson Comorbidity Index ( P < 0.001), and with creatinine levels ( P = 0.007), previous cardiac surgery ( P < 0.001), diabetes mellitus ( P = 0.02), haemoglobin value ( P = 0.004), pulmonary capillary wedge and central venous pressures ( P = 0.019 and 0.01, respectively), systolic and mean pulmonary artery pressures ( P = 0.002 and 0.014, respectively). The rate of 30-day mortality from the lowest to the highest RDW tertile was 1.4, 4 and 9% ( P = 0.02), respectively. Long-term mortality correlated at multivariate analysis with recipient age [hazard ratio 1.06, 95% confidence interval (95% CI) 1.02–1.09], donor age (hazard ratio 1.02, 95% CI 1.0–1.04) and RDW (hazard ratio 1.13, 95% CI 1.04–1.23). The survival probability at 4, 8 and 12 years was 90, 84 and 74% for recipients with RDW less than 14.6%, while it was 72, 60 and 42% for recipients with RDW more than 16.4% (hazard ratio 3.29, 95% CI 1.74–6.24). No differences were found between causes of death. Conclusion: RDW correlated with survival in HTx recipients. This marker of blood cell size may represent a surrogate of disease and a helpful tool in the risk-assessment process.